PENETAPAN AHLI WARIS BERDASARKAN PERKARA NOMOR 0280/Pdt.G/2015/PA.Pbr TANPA WASIAT KEPADA AHLI WARIS - Muhammad Noer Geo Miyana; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Chronological case number: 0675 / PdtG / 2013 / PA.Pbr. June 20, 2014, the late Hj. Sofiah binti Edek who own property together as husband and wife, in the form of a piece of land and its permanent building on teletak in Jalan Rajawali No. 62, RT.02, RW 04, Village Kedung Sari, District Sukajadi, Pekanbaru. The purpose of this thesis, namely; First, to determine the consideration of judges on case No. 0280 / Pdt.G / 2015 / PA. Pbr intestate heirs, Secondly, to find out the judge's decision was appropriate according to Islamic law.This type of study can be classified in this type of normative juridical research, which is a type of research that discusses the principles of law. This research was conducted by examining the library materials or secondary data in the form of legislation and the books written by legal experts associated with the title of the research, articles, journals, and other sources. Federally data sources used, the primary data, secondary data and data tesier, data collection techniques in this study with the study of literature or documentary studies.Based on the research there are two principal issues that can be inferred. First,Based on legal considerations and basic provisions of the law are used, the judge ruled that the right to be heir consists of four (4) persons younger boys and four (4) girls are Hj. Nurjanah bint Khalib Dain girls, Nurman bin Khalib Dain son-worthy, Nurhadi bin Khalib Dain son, Muhammad Aini bin Khalib Dain son, Rosma bint Khalib Dain daughter, Nurhayati binti Khalib Dain girls, Jamaluddin bin Khalib Dain son and daughter Khalib Dain Jaliah girls who all reside diPekanbaru. Second, the judge's decision on case No.0280 / Pdt.G / 2015 / PA.Pbrthere needs to be corrected according to Islamic law and contains the value or the quality of legal certainty. Land Hj. Sopiah bint Edek number of 325.08 m2 while the verdict of land distributed to the heirs of 324 m2, the division of the estate Hj. Edek and Sopiah binti Hj. Nurjanah bint Khalib first plaintiff who had died on Saturday 04th of April 2015. Based on the case that the Islamic law of inheritance, the heirs male resident balanced by the heiress in accordance with the position and function in families where male heir and women gained the right to a comparison 2: 1 (two to one). Suggestions Author, First Should the division of the inheritance of each heir can finish it amicably, because not a few families divided because of the division of the inheritance. Second, Sebeium apply to court and claim inheritance should know in advance where the heirs and follow the procedures in the Religious Court. Keywords : Islamic Inheritance - Legal Considerations - Religious Court